Psychophysiological Analysis of the Influence of Vasopressin on Speech in Patients with Post-Stroke Aphasias - Tsikunov, Sergei G.; Belokoskova, Svetlana G. (The Spanish Journal of Psychology, 2007)
Speech is an attribute of the human species. Central speech disorders following stroke are unique models for the investigation of the organization of speech. Achievements in neurobiology suggest that there are possible neuroendocrine mechanisms involved in the organization of speech. It is known that the neuropeptide vasotocin, analogous of vasopressin in mammals, modulates various components of vocalization in animals. Furthermore, the positive influence of vasopressin on memory, which plays an important role in the formation of speech, has been described. In this study, speech organization processes and their recovery with the administration of vasopressin (1-desamino-8-D-arginin-vasopressin) to 26 patients with chronic aphasias after stroke were investigated. Results showed that sub endocrine doses of the neuropeptide with intranasal administration had positive influence primarily on simple forms of speech and secondarily on composite forms. There were no statistically significant differences between the sensory and integrative components of the organization of speech processes with vasopressin. In all cases, the positive effect of the neuropeptide was demonstrated. As a result of the effects, speech regulated by both brain hemispheres improved. It is suggested that the neuropeptide optimizes the activity both in the left and right hemispheres, with primary influence on the right hemisphere. The persistence of the acquired effects is explained by an induction of compensatory processes resulting in the reorganization of the intra-central connections by vasopressin.
Keywords: Speech; Functional asymmetry; Aphasia; Vasopressin